PEKERJA RUMAH TANGGA ANAK - Endang Abdullah (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2011)
State going forward, if feasible educated human resources. Distribution educated person should be comprehensive and balanced, both in urban and rural areas, in government or in private company, and on the politician or the technician. But atthis moment felt quite expensive education costs, especially faced by the poor. Phenomenon in society, children of school agemcan not even school, because of the inability of parents and families to finance their children's schooling, even children trapped into child household helper (PRTA) to meet the needs of family life. Efforts to alleviate this PRTA confectionary serious need of all parties, in this case the Government, private organizations, activists, the law enforcement officials and politicians, through various methods of comprehensive and systemic.